Acute Liver Failure Occurring during the First Trimester of Pregnancy Successfully Treated with Living Donor Liver Transplantation. (4th December 2013) - Kanogawa, Naoya; Kanda, Tatsuo; Ohtsuka, Masayuki; Nakamura, Masato; Miyamura, Tatsuo; Yasui, Shin; Arai, Makoto; Maruyama, Hitoshi; Fujiwara, Keiichi; Shozu, Makio; Oda, Shigeto; Miyazaki, Masaru; et al.
Abstract : Acute liver failure (ALF) during pregnancy remains difficult to treat, and despite advances in treatment, liver transplantation must be selected as treatment option in certain cases. We report a 30-year-old woman with ALF of unknown etiology, occurring during the first trimester of pregnancy. Her condition was complicated by consciousness disturbance and coagulopathy due to ALF, but she was successfully treated with living donor liver transplantation 7 days after dilatation and curettage. At 9-month followup, she was in good medical condition. Liver transplantation has been reported as one of the treatment options for ALF during pregnancy with the prognosis varying depending on the trimester, from living donor or deceased donor liver transplantation. Of importance is that clinicians always think of emergent liver transplantation as a therapeutic option in ALF even in the first trimester of pregnancy.